Gestational di-(2-ethylhexyl) phthalate exposure causes fetal intrauterine growth restriction through disturbing placental thyroid hormone receptor signaling. (15th September 2018) - Yu, Zhen; Han, Yan; Shen, Ru; Huang, Kun; Xu, Yuan-yuan; Wang, Qu-nan; Zhou, Shan-shan; Xu, De-xiang; Tao, Fang-biao
Graphical abstract: Highlights: Gestational DEHP exposure causes fetal IUGR in a dose-dependent manner. Gestational DEHP exposure disturbs placental THR signaling. Gestational DEHP exposure disturbs placental angiogenesis. Placental microvessels density is lower in SGA cases from MABC Birth Cohort. THRs protein abundance is reduced in SGA cases. Abstract: Previous study reported that gestational Di-(2-ethylhexyl) phthalate (DEHP) exposure caused fetal intrauterine growth restriction (IUGR). We aimed to investigate the role of placental thyroid hormone receptor (THR) signaling in DEHP-induced IUGR. Dams were treated with DEHP (50 or 200 mg/kg) by gavage daily throughout pregnancy. As expected, gestational DEHP exposure dose-dependently caused fetal IUGR. The mRNA levels of placental Thrα1 and Thrβ1 were reduced and nuclear translocation of placental THRα1 and THRβ1 were suppressed in DEHP-exposed mice even though thyroid hormones in maternal and fetal sera were unaffected. Correspondingly, Vegf, Pgf, Igf1 and Igf2, several THR downstream genes essential for placental angiogenesis, were down-regulated in placenta of DEHP-exposed mice. Histopathology showed that vascular space in the labyrinthine region was shrunken in placenta of DEHP-treated mice. The microvessel density in labyrinthine region was reduced in DEHP-treated mice. A nested case-control study based on MABC suggested that microvessel density was decreased in placenta of SGA cases. Moreover, protein abundance of placental THRα1 and THRβ1 were lower in SGA cases. In conclusion, gestational DEHP exposure increases fetal IUGR incidence through disturbing placental THR signaling. The present study, at least partially, elucidate the underlying mechanism of DEHP-induced fetal IUGR.